Urban Competition in a regional development Project with a sustainable perspective - Mustafa Oguz Sinemillioglu (European Regional Science Association (ERSA), 2003)
During the development mentality Regional Development has been a vital subject in planing. Besides Regional Disparities have been and raiseing on together with the Regional development programs and projects. in this study, It will be compared three cities whose populations is among 500 000 and 1 Milion inhabitants with their population movements, economic development, Structural urban changes and social facilities in a sustainable perspective. Southeastern Anatolia Project in which the cities are located is the biggest regional development project ever carried out in Turkey, And Gaziantep by far the biggest city in the project has a leading role not only in industry but also in commercial facilities. Besides all the cities are taking migrations and so the problems like infrastructure and lack of housing etc. After analyzing the projects development and cities evolutions it will be compared cities capabilities and its effects not only to each other but also to their hinterland. Conclusion will focus on the effects of regional Developments and its Comprehensiveness.
Keywords: 330